Technology Review of Automated Emergency Braking Pedestrian System for Selected Vehicles in Global Market - M.A. Meor Said; A.N. Abu Kassim; N.H.F. Ismail; M.S.F. Mansor; M.Z. Che Mustafa; R. Rani (Journal of the Society of Automotive Engineers Malaysia, 2022)
Accidents involving vehicle and pedestrian has been on the rise, in line with the ever-increasing number of vehicles on the road. Autonomous Emergency Braking (AEB) Pedestrian System is designed to prevent such accidents with the use of sensors and an intelligent system that makes quick action to apply braking force to a vehicle, automatically. The objective of this paper is to report a technology review performed on current Autonomous Emergency Braking Pedestrian systems based on information from owner’s manuals, journal papers, and internet resources. 16 different vehicle models that were investigated for this technology review, consisting of a sedan, hatchback, and SUV were investigated based on their differences, similarities, advantages, and disadvantages. Four areas of specifications are highlighted, which are working speed, detection systems, limitations, and special features. Current research done on improving the AEB Pedestrian system is also being reviewed, where Artificial Intelligent tools such as Deep-reinforced Learning are being developed to enhance image processing systems for better detection of Vulnerable Road Users (VRUs), especially in different road conditions, weather, and other circumstances.